- #26

SammyS

Staff Emeritus

Science Advisor

Homework Helper

Gold Member

- 11,348

- 1,022

Enclose the entire denominator in parentheses.Okay, I think I have it now: (x^{2}+ 2x + 1)/(18cw^{3}) times (12c^{3}w)/(x^{2}-1) = (x+1)^{2}(12c^{3}w)/(18cw^{2})(x+1)(x-1) Cancel the (x+1) = (12c^{3}w)(x+1)/(18cw^{2})(x-1) Cancel the c and w = (12c^{2})(x+1)/(18w)(x-1) divided by 3 (numerator and denominator) = (4c^{2})(x+1)/(6w)(x-1) divided by 2 (numerator and denominator) = (2c^{2})(x+1)/(3w)(x-1) Answer

(2c

^{2})(x+1)/

**(**(3w)(x-1)

**)**.